The Circular Structure of the Legal System and the Comprehension of norms as an agreement of sense - Vázquez Esquivel, Efrén (Crítica Jurídica. Revista Latinoamericana de Política, Filosofía y Derecho, 2013)
The present essay has the main objective of analyzing the ways and possibilities of a hermeneutically oriented interpretation of legal norms, as an adequate manner of comprehending and applying them correctly. For this purpose, I will base this work on W. Dilthey’s and M. Heidegger’s contributions in reference of the hermeneutical circle, the interpretation and comprehension to the science of the spirit.Applying them to the interpretation of legal norms